2008
DOI: 10.1073/pnas.0806306105
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and functional divergence between the cystic fibrosis transmembrane conductance regulator and related ATP-binding cassette transporters

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a member of the ATP-binding cassette (ABC) transporter superfamily, an ancient family of proteins found in all phyla. In nearly all cases, ABC proteins are transporters that couple the hydrolysis of ATP to the transmembrane movement of substrate via an alternating access mechanism. In contrast, CFTR is best known for its activity as an ATP-dependent chloride channel. We asked why CFTR, which shares the domain architecture of ABC proteins that fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 29 publications
5
70
3
Order By: Relevance
“…However, our finding that the increase in R352C macroscopic current amplitude that results from modification by MTSET is significantly larger when measured at Ϫ80 mV compared with ϩ80 mV (Figs. 2 and 3) seems initially in conflict with the suggestion that this arginine normally interacts with Asp-993 in TM9 (37,38) and is instead more consistent with our previous suggestion that this arginine residue normally forms an accessible surface charge near the inner mouth of the pore (11). However, as pointed out by Alexander et al (30), these two suggestions are not necessarily irreconcilable; they suggested that the role of Arg-352 may be to neutralize the effect of an exposed negative charge contributed by the Asp-993 side chain.…”
Section: Discussioncontrasting
confidence: 54%
“…However, our finding that the increase in R352C macroscopic current amplitude that results from modification by MTSET is significantly larger when measured at Ϫ80 mV compared with ϩ80 mV (Figs. 2 and 3) seems initially in conflict with the suggestion that this arginine normally interacts with Asp-993 in TM9 (37,38) and is instead more consistent with our previous suggestion that this arginine residue normally forms an accessible surface charge near the inner mouth of the pore (11). However, as pointed out by Alexander et al (30), these two suggestions are not necessarily irreconcilable; they suggested that the role of Arg-352 may be to neutralize the effect of an exposed negative charge contributed by the Asp-993 side chain.…”
Section: Discussioncontrasting
confidence: 54%
“…Kirk 2008;Jordan et al 2008). This proposition is supported by a very recent report providing strong evidence that the gate of CFTR is indeed located more to the extracellular part of the pore (Bai et al 2011;but cf.…”
mentioning
confidence: 99%
“…However, the crystal structures of multiple ABC transporters including the p-glycoprotein have been www.intechopen.com solved (Locher et al, 2002;Dawson & Locher, 2006;Aller et al, 2009). Attempts to use these structures as bases for modeling full-length CFTR have provided new insights into the role of F508 residue in domain-domain interactions (Jordan et al, 2008;Loo et al, 2008;Serohijos et al, 2008a;Mornon et al, 2009). These studies, when backed up by biochemical analyses, are an excellent start point to probe F508 global conformational defects and their repair.…”
Section: Conformational Repair: One Stone and Three Birdsmentioning
confidence: 99%